1998
DOI: 10.1080/09629359891324
|View full text |Cite
|
Sign up to set email alerts
|

Rooperol tetraacetate decreases cytokine mRNA levels and binding capacity of transcription factors in U937 cells

Abstract: We have previously described inhibition of the synthesis of three acute-phase inflammatory cytokines in human and rat macrophages by acetate esters of rooperol, a dicatechol of plant origin. Analysing the mechanism of anticytokine activity of rooperol, we compared levels of TNFalpha, IL-1beta and IL-6 mRNAs in the human promonocytic U937 cell line pretreated with phorbol myristate acetate (PMA) and incubated with rooperol tetraacetate (RTA) alone or in combination with LPS (500 ng/ml). It was found that 10 mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…In fact, the TNF-α 308.2 SNP or rs1800629(AA), translating into an increased transcription of the TNF-α gene ( 55 ), has been shown to correlate with a more severe hepatic fibrosis during S. mansoni infections ( 54 ). The picture is a clearly more nuanced as a study in Uganda observed a differential association between INF-ɤ, TNF-α and fibrosis ( 86 ) where TNF-α reportedly acted by balancing the protective effect of INF-ɤ ( 87 ); a trend confirmed in Zambia ( 51 ). Overall, adding to observations in experimental models, a strong case is made for INF-ɤ as an anti-fibrotic cytokine ( 11 , 30 ), whereas TNF-α (also produced by Th1 cells and macrophages) primarily appears to aggravate hepatic fibrosis during schistosomiasis ( 87 ).…”
Section: Humans Factors Associated With Liver Fibrosis During Schistomentioning
confidence: 99%
“…In fact, the TNF-α 308.2 SNP or rs1800629(AA), translating into an increased transcription of the TNF-α gene ( 55 ), has been shown to correlate with a more severe hepatic fibrosis during S. mansoni infections ( 54 ). The picture is a clearly more nuanced as a study in Uganda observed a differential association between INF-ɤ, TNF-α and fibrosis ( 86 ) where TNF-α reportedly acted by balancing the protective effect of INF-ɤ ( 87 ); a trend confirmed in Zambia ( 51 ). Overall, adding to observations in experimental models, a strong case is made for INF-ɤ as an anti-fibrotic cytokine ( 11 , 30 ), whereas TNF-α (also produced by Th1 cells and macrophages) primarily appears to aggravate hepatic fibrosis during schistosomiasis ( 87 ).…”
Section: Humans Factors Associated With Liver Fibrosis During Schistomentioning
confidence: 99%
“…[36] Rooperol, the aglycone of the major phenolic constituent of H. rooperi corms, has been shown to inhibit cytokine mRNA levels in LPS-stimulated U937 cells. [37] DRS binding and inhibition of p38a by rooperol demonstrated here may play a role in the anti-inflammatory effects of this natural product.…”
mentioning
confidence: 61%
“…Incubation of p38a (5 mm) with 3 (100 mm) was carried out in the presence of individual members of a small library of plant polyphenol natural products and synthetic analogs, each at 200 mm, for 16 h. The reaction mixtures were subjected to click reaction conditions and in-gel fluorescence analysis, and the inhibition of adduct formation by 3 was determined by quantification of the fluorescence bands (Figure 7). Within this limited number of compounds, the African potato (Hypoxis rooperi)-derived rooperol [36] shows the strongest inhibition, followed closely by the honey bee propolis-derived caffeic acid phenethyl ester (CAPE [37] ) and its double-bond reduced analog DHC. Other synthetic analogues of CAPE (e.g., the corresponding amide, CAPA) and other H. rooperi-derived natural products (e.g., nyasol) are much less effective inhibitors (Figure 7).…”
mentioning
confidence: 99%
“…Subsequent studies revealed that RTA may inhibit cytokine synthesis in promonocytic U937 cell line at the pretranslational level. 8 All those results suggested that rooperol esters are potential anti-in ammatory drugs.…”
Section: Discussionmentioning
confidence: 97%
“…6,7 We recently demonstrated that rooperol, a plant dicatechol, decreases production of tumour necrosis factor (TNFa), interleukin-1 (IL-1) and interleukin-6 (IL-6) in LPS-stimulated human and rat macrophages and NO production in rat macrophages. 7,8 Here we describe the effect of rooperol tetraacetate on the respiratory burst in human and rat phagocytes. Twenty ml of whole bood was taken from the nger of healthy volunteers (25± 48 years of age) and used immediately for respiratory burst measurement.…”
Section: Introductionmentioning
confidence: 99%